2011
DOI: 10.1589/rika.26.679
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fatigued Hip Abductors on Single-Leg Stance Postural Control and Muscle Control

Abstract: [Purpose] The purpose of this study was to clarify postural control and muscle activity of the gluteus medius and musculus erector spinae in a single-leg stance before and after hip muscle abductor fatigue.[Subjects] Subjects were 22 healthy male adults (mean age; 21.4 yrs) with no significant medical history or current medical problems.[Methods] We examined postural control and muscle activity in a single-leg standing position before and after hip muscle abductor fatigue. A statistical analysis was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…These studies suggest that intensive walking exercises cause muscle fatigue in the whole body and legs and affect the COGS. On the other hand, Matsuda et al [9] reported that, although the X-axis trajectory length was affected by the hip abduction muscle fatigue, the Y-axis trajectory length remained unchanged. Here, both before/after (COP displacement in anterior-posterior; COP-AP) and left/right (medial-lateral; COP-ML) directions were affected, similarly to the data obtained during a walking exercise on a treadmill by Selthafner et al [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies suggest that intensive walking exercises cause muscle fatigue in the whole body and legs and affect the COGS. On the other hand, Matsuda et al [9] reported that, although the X-axis trajectory length was affected by the hip abduction muscle fatigue, the Y-axis trajectory length remained unchanged. Here, both before/after (COP displacement in anterior-posterior; COP-AP) and left/right (medial-lateral; COP-ML) directions were affected, similarly to the data obtained during a walking exercise on a treadmill by Selthafner et al [15].…”
Section: Discussionmentioning
confidence: 99%
“…The balance function and leg strength are also involved in maintaining a stable posture [7]. During aging, the COGS is affected by the decline of nervous functions [8] and decreased leg strength [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation